PENERAPAN PENDEKATAN TaRL BERBASIS MODEL PEMBELAJARAN BASED LEARNING DENGAN MEDIA PEMBELAJARAN WORD WALL UNTUK MENINGKATKAN KEAKTIFAN PESERTA DIDIK - Rukmana Putri, Radianti; Rodiyana, Roni; Natalia, Dwi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research is motivated by the low level of learning of students at SDN Dupak 1 Surabaya because the learning methods used by teachers are less varied, namely lectures and questions and answers, so that students are less active in learning activities. The use of the Teaching at the Right Level (TaRL) approach based on Problem Based Learning (PBL) towards the use of the PBL learning model is intended so that students play a greater role in solving problems actively and collaboratively in their group members. Therefore, there needs to be innovative learning that encourages students to be actively involved in the learning process, namely the use of wordwall learning media. PTK is carried out with four important stages, namely observation, observation, test results through learning quizzes, and documentation. Classroom action research with research subjects of class IV-D students at SDN Dupak 1 Surabaya totaling 25 students consisting of 14 males and 11 females. The data collection method in this study used observation and documentation. The instrument used was the student activity observation sheet.